Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Let's say that $$x_{1} \gt 0$$ We define the sequence by the formula $$x_{n+1} = - \ln(x_{1} +x_{2}+x_{3}+\dots+x_{n}) $$ Prove that the series $$\sum_{n=2}^{ \infty } x_{n}$$ is convergent and find the sum of it.

My attempt was to use the identity $$\ln(1+x)\lt x$$ somehow, but without any results. I've also determined that the elements of the sequence are positive and that $$x_{n+1} = - \ln(x_{1} +x_{2}+x_{3}+\dots+x_{n}) = \ln\left(\frac{1}{x_{1} +x_{2}+x_{3}+\dots+x_{n}}\right)$$

share|cite|improve this question
So we have $x_{n+1}=-\ln(x_1-\ln x_1-\ln(x_1-\ln x_1)-\ln(x_1-\ln x_1-\ln(x_1-\ln x_1))-\dots$ – abiessu Jan 8 '14 at 20:38
The elements of the sequence are not necessarily positive, unless $0\le x_1\lt 1$. If $x_1\gt1$, then $x_2=-\ln(x_1)$ is negative. – Barry Cipra Jan 8 '14 at 20:41
One simple observation: If the series converges, then $x_n\to0$. It follows from the assumed identity that the sum of the series is $e^0=1$. – Harald Hanche-Olsen Jan 8 '14 at 20:48

Let $s_n=\sum _{k=1}^n x_k$ for $n\geq 1$. Then $s_{n+1}=s_n-\log(s_n)$. So it comes down to showing that iterating $x\mapsto x-\log(x)$ converges when you start with some positive $x$. Now use that $x-\log(x) \geq 1$ with equality only for $x=1$ and that $1<x-\log(x)<x$ for $x>1$.

share|cite|improve this answer
Ah, of course! You nailed it. – Harald Hanche-Olsen Jan 8 '14 at 20:51
In this case, the partial sum is more than the sum of its parts... – robjohn Jan 8 '14 at 21:52
Immeasurable comment. – copper.hat Jan 8 '14 at 21:56

We have $e^{-x_{n+1}} = x_1+...+x_n \ge 1-x_{n+1}$. Hence $x_1+...+x_n + x_{n+1} \ge 1$, and consequently, $x_{n+1} \le 0$ for all $n>1$.

Hence the sequence $x_1+...+x_{n+1}$ is non-increasing and bounded below, so it converges. Since it converges, $x_n \to 0$, from which it follows that $x_1+...+x_n = e^{-x_{n+1}} \to 1$.

share|cite|improve this answer
To atone for my earlier contractive sins... – copper.hat Jan 8 '14 at 21:42

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.